Examining consumer behavior using social media instagram in marketing 4.0 era based on customer path 5a - Ni Putu Ayu Cintya Dewi; Ida Bagus Raka Suardana (Institut Pariwisata dan Bisnis Internasional, 2021)
The purpose of this study was to determine the consumer behavior of Instagram users in Marketing 4.0 based on Customer Path 5A. Data collection techniques used observation and in- depth interview , with health protocols implemantation in New Normal. Stages in data analysis include data reduction (data reduction), presenting data (data display) and drawing conclusions and verification (conclusion drawing / verification). Based on the results of research conducted on four NSB Beauty Studio customers who use social media Instagram, the conclusion of consumer purchasing decisions for NSB Beauty Studio service have basically through all stages of Customer Path 5A, starting from problem recognition to post-purchase behavior about Aware, Appeal, Ask, Act, and Advocate. All informants also said that Instagram helped them get to aware and make purchases of the NSB Beauty Studio brand.